INTERPRETASI YANG SALAH MENGENAI BUSINESS JUDGMENT RULE PADA SUBSTANSI DAN STRUKTUR HUKUM DI INDONESIA - Williem Darmawangsa (UNES Law Review, 2023)
Indonesia views SOEs and their subsidiaries as companies operating in the public sector, even though on the other hand, SOEs and their subsidiaries are companies formed as limited liability corporations. As a legal entity, there are legal consequences that give the corporation the ability to have its own assets and wealth, which should rightfully belong to humans. Although a legal entity cannot act on its own, it can establish its governing body, in this case, the Board of Directors. However, the government's view of SOEs and their subsidiaries as a public legal entity has caused conflicts, namely, how the legal accountability of the Directors of SOEs and their subsidiaries is determined in making business decisions and what standards of Business Judgment Rule violations lead to losses to be borne by the Directors.